"Indeterminate" UroVysion Fluorescence In Situ Hybridization Results: Clinical Implications of Diagnostic Terminology. Issue 3 (6th March 2021) - Xu, Jing; Westfall, Danielle E; Lopategui, Jean R
Abstract: Objectives: UroVysion cases with one to three abnormal cells that do not meet the threshold for positivity may be better classified as "indeterminate." The aim of this study is to determine the incidence and clinical significance of these indeterminate UroVysion results. Methods: The UroVysion fluorescence in situ hybridization (FISH) results over a 4-year period in our institution were retrospectively analyzed. Follow-up of the initial UroVysion cases, including urine cytology or bladder biopsy performed within 12 months of the initial diagnosis of the result, was obtained from pathology reports. Results: A significant fraction (178 of 1, 907, 9.3%) of the UroVysion cases had indeterminate results. Overall, the subsequent malignancy rate of the group with indeterminate UroVysion results (14 of 59, 23.7%) was higher than the group with normal results (48 of 319, 15.0%), although the difference was not significant ( P  = .124). For patients without a history of urinary tract neoplasm, the subsequent malignancy rate in the group with indeterminate results (7 of 18, 38.9%) was significantly higher than the group with normal results (16 of 103, 15.5%) ( P  = .044). Conclusions: Our results support that indeterminate UroVysion FISH result may warrant closer clinical follow-up in patients without a history of urinary tract neoplasm. We suggest reporting these cases as "aneusomy of undetermined significance."